Engel im Herrscherbild?: zur Assimilation abendländischer Motive in der höfischen Miniaturmalerei Indiens im 16. und 17. Jahrhundert - Juneja, Monica (Jahrbuch für Geschichte Lateinamerikas, 1999)
This paper seeks to examine the encounter between European and non- European cultures as a two-way, dynamic process in which the colonised non-European culture, though ostensibly a recipient of „outside influences", is rarely ever a passive element in this relationship. The structure and forms of one such encounter are brought into focus through a case study of miniature painting at the Mughal court in North India during the 16'h and 17'h centuries, and the ways in which it responded to European art forms and motifs. What were the factors and processes shaping the selective appropriation, reworking and assimilation of Christian iconography and the Renaissance principles within the structures of Mughal art?
Online veröffentlicht: Sep 2021
Gesehen am 06.07.2023